Fungal allergic sensitisation in young rural Zimbabwean children: Gut mycobiome and seroreactivity characteristics - Lorraine Tsitsi Pfavayi (Elsevier, 2021)
Summary: Background: The prevalence of allergic diseases has increased over the last few decades, with sensitisation to fungal allergens and gut microbiome dysbiosis implicated in this trend. The fungal community in the gut (mycobiome) has yet to be characterised and related to fungal allergic sensitisation. Thus, we characterised the gut mycobiome and related it to fungal sensitisation and seroreactivity among Zimbabwean children. We further determined the effect of host age, sex, Schistosoma haematobium infection and mycobiome composition on fungal sensitisation and seroreactivity. Methods: Using shotgun metagenomic sequencing, we characterised the gut microbiome of stool samples of 116 preschool aged children (PSAC) (≤5 years old, 57(49.1%) male and 59 (50.9%) female). Sensitisation to common fungi in Zimbabwe was assessed using skin prick tests (SPTs). Allergen-specific IgM, IgA, IgG, IgE and IgG4 antibodies were quantified by ELISA. We analysed the relationship between fungal genera and SPT reactivity by ANOVA; fungal genera and IgE antibody reactivity by linear regression; variation in mycobiome abundance with host and environmental factors by PERMANOVA; SPT reactivity and host and environmental factors by logistic regression; seroreactivity and host and environmental factors by ANOVA. Results: The mycobiome formed <1% of the sequenced gut microbiome and 228 fungal genera were identified. The most abundant genera detected were Protomyces, Taphrina, and Aspergillus. S.haematobium infection had a significant effect on fungal genera. Prevalence of SPT sensitisation to ≥1 fungal species was 96%, and individuals were frequently sensitised to Saccharomyces cerevisiae. Antibodies were detected in 100% of the population. There was no relationship between mycobiome abundance and IgE titres or IgE/IgG4 ratios for each fungal species; no significant differences between SPT reactivity and abundance of fungal species except for S. cerevisiae; and fungal seroreactivity did not significantly differ with age. There were some sex (m>f for, Epicoccum nigrum and Penicillium chrysogenum) and SPT reactivity –related differences in seroreactivity. Conclusion: This is the first comprehensive characterisation of gut mycobiome and fungal allergic sensitisation of rural children in Zimbabwe. Although reported allergic disease is low there is a high percentage of sensitisation. Further studies with larger populations are required to understand the role of the mycobiome in allergic diseases.